DIGITAL TRANSFORMATION INDUSTRY 4.0 AND OPERATIONAL EXCELLENCE ON SMALL AND MEDIUM ENTERPRISES (SMES) IN MALAYSIA - Muhammad Yushafiq Yusri; Mohd Hafeez Al-Amin Abdul Wahabo; Abdul Aziz Yaacob; Che Mohd Syaharuddin Che Cob; Siti Nur Zahirah Omar (International Journal of Accounting, Finance and Business, 2024)
Despite small and medium enterprises (SMEs) manufacturing sectors is the largest contributor to the total exports and the second largest contributor to the gross domestic product (GDP) in Malaysia, SMEs are affected by the challenges from the business environment which influence their performance. The purpose of this study was to discusses the relationship between digital transformation industry 4.0 (I4.0) and operational excellence on SMEs manufacturing sectors in Malaysia. The present study is a literature review on the effect of digital transformation industry 4.0 (I4.0) on operational excellence in SMEs manufacturing sectors in Malaysia. This study attempts to help SMEs manufacturing sectors in Malaysia to adopt digital transformation industry 4.0 (I4.0) to remain significantly achieve sustainable operations for operational excellence in the business environment. The practical application of digital transformation industry 4.0 (I4.0) will help SMEs to attain an operational excellence with greater efficiency and productivity in their overall business performance